Adherence of Drug Promotional Literatures Distributed by Pharmaceutical Companies to World Health Organization Ethical Criteria for Medicinal Drug Promotion - Prasad, Pravin; Bajracharya, Sangha Ratna; Deo, Satish; Lamichhane, Samir; Pradhan, Pranil Man Singh; Ghimire, Rakesh; Pokharel, Akritee (Journal of Nepal Health Research Council, 2019)
Background: Drug Promotional Literatures are usually relied upon for drug promotion, however studies have shown them to contain several pitfalls. World Health Organization has time and often revised the guideline to address the issue and World Health Organization Ethical Criteria for Medicinal Drug Promotion was established. Based on this guideline, several regional as well as national guidelines have been formulated. Though laws to regulate drug promotion is existent, studies have shown problems with drug promotional literatures in Nepal also. This study was carried out to analyse the drug promotional literatures distributed by pharmaceutical companies in Nepal as per World Health Organization Ethical Criteria for Medicinal Drug Promotion. Methods: A cross-sectional study over a period of one year was conducted at our department. Pharmaceutical companies registered in Department of Drug Administration, Kathmandu and consenting for the study were requested to provide ten unique drug promotional literatures of their products. Collected drug promotional literatures were analysed for inclusion of essential information as per World Health Organization Ethical Criteria for Medicinal Drug Promotion, level of biasness. Different drug promotional literatures were also classified and compared for these aspects. Results: A total of 48 pharmaceutical companies were included in the study. Drug promotional literatures (n = 372) were analysed during the study. Adherence to criteria concerned with positive attributes of the promoted medicine was found to be higher, most of the drug promotional literatures adhered to 5-8 criteria of World Health Organization Ethical Criteria for Medicinal Drug Promotion and were categorised into grade B. Difference in adherence as well as number of biased drug promotional literatures was also seen when drug promotional literatures were compared on different basis. Conclusions: Adherence to World Health Organization Ethical Criteria for Medicinal Drug Promotion was found to vary when drug promotional literatures were classified as per pharmaceutical company, type of formulation being promoted, type of drug promotional literatures. Keywords: Drug act Nepal 1978; drug promotional literatures; WHO-ethical drug criteria for medicinal drug promotion.